Studies of boundaries and interfaces on the atomic scale by atom probe FIM - Smith, G; Cerezo, A; Godfrey, T; Seto, K; Warren, P (1998)
This paper describes recent developments in the experimental methods of atom probe field ion microscopy, and in particular the means for the three-dimensional reconstruction of the atomic chemistry of solids. A selection of applications is presented, involving the study of grain boundary and interface phenomena. Topics discussed are segregation to grain boundaries in ultra-low carbon steels; the reconstruction of atomic plane configurations in a tungsten bicrystal; and the partitioning and redistribution of solute in the region of an interphase interface in a rhenium-containing nickel-base superalloy. The ability of the atom probe to provide quantitative chemical analysis on the nanometre scale is emphasised.